Penggunaan Teknologi dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Wardani, Ayu Kusuma; Hamzah, Rahma Ashari; Adam, Andi Ahmad Harullah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The teaching of Indonesian in elementary schools is one area of education that is drastically changing in the digital age. It has been demonstrated that incorporating technology into language instruction improves instructional efficacy, enriches students' literacy experiences, and makes learning more engaging and individualized. By looking at numerous scholarly sources from the previous five years about the use of technology in Indonesian language learning, this study uses a literature review methodology. The findings of the study demonstrate that the use of technology, including digital libraries, augmented reality (AR), e-books, and applications based on artificial intelligence, helps students improve their language proficiency in speaking, writing, listening, and reading. Additionally, technology contributes to learning assessment by enabling more efficient and objective evaluations through digital platforms. Nonetheless, there are still issues with technology adoption, including the digital divide, infrastructure preparedness, and teachers' proficiency in making the most of technology. Thus, in order to enhance the quality of Indonesian language instruction in elementary schools, a thorough approach to technology integration is required.